(untitled) (Research, Society and Development, 2022)
Currently, Brazil is the largest exporter and producer of coffee in the world, and it is the second most consumed beverage in the world, only behind water. In the years 2019 and 2020 it is estimated that the world consumption of coffee was 168.84 million bags of 60 kg, Brazil consumed 20 million bags of coffee, the second-largest consumer in the world, only behind the United States with 25 million bags. The techniques such as infrared spectroscopy has been applied in the food industry, as it is a fast, easy technique, without the need for reagents, free from polluting processes, and capable of analyzing the simultaneous composition of the constituents. The present study aims to analyze the changes in the chemical constituents of Brazilian commercial coffees as a function of shelf life through Fourier transformed infrared spectroscopy (FT-IR) associated with chemometric methods. The experiments were carried out within the expiration date, 6 months, and a year after the expiration date. Spectra were obtained in the range from 4000 to 500 cm-1. The studies of Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) were made as discrimination methods. The areas in the region from 2970 to 2830 cm-1 and 1765 to 1720 cm-1 were calculated to analyze the alteration as a function over time. The results suggest that these bands in coffee are sensitive over time and to the storage conditions, promoting changes in aroma and flavor.